2018
DOI: 10.1051/0004-6361/201832983
|View full text |Cite
|
Sign up to set email alerts
|

The perturbed sublimation rim of the dust disk around the post-AGB binary IRAS08544-4431

Abstract: Context. Post-Asymptotic Giant Branch (AGB) binaries are surrounded by stable dusty and gaseous disks similar to the ones around young stellar objects. Whereas significant effort is spent on modeling observations of disks around young stellar objects, the disks around post-AGB binaries receive significantly less attention, even though they pose significant constraints on theories of disk physics and binary evolution. Aims. We want to examine the structure of and phenomena at play in circumbinary disks around p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(81 citation statements)
references
References 61 publications
(76 reference statements)
4
77
0
Order By: Relevance
“…This results in unreliable distances for some of our stars. Nevertheless, the distances from Gaia have been shown to agree fairly well with other distance measurements in some cases, such as IRAS 08544-4431 (Kluska et al 2018), RV Tau and DF Cyg , and GK Car and GZ Nor . For other cases, the parallax measurement from Gaia is highly likely to be affected by the binary motion.…”
Section: Luminosity Determinationsupporting
confidence: 65%
“…This results in unreliable distances for some of our stars. Nevertheless, the distances from Gaia have been shown to agree fairly well with other distance measurements in some cases, such as IRAS 08544-4431 (Kluska et al 2018), RV Tau and DF Cyg , and GK Car and GZ Nor . For other cases, the parallax measurement from Gaia is highly likely to be affected by the binary motion.…”
Section: Luminosity Determinationsupporting
confidence: 65%
“…The here presented survey (see Figs. C.1 and C.2) and our imaging campaign of IRAS 08544-4431 (Hillen et al 2016;Kluska et al 2018) have demonstrated the potential of near-infrared interferometric images, have shown which targets can be well resolved with the existing instrumentation and which are most interesting for follow-up campaigns.…”
Section: Discussionmentioning
confidence: 76%
“…Despite very different forming processes, pAGB disks are in many ways (infrared excess, Keplerian rotation, winds, dust mass, dust mineralogy and grain sizes) similar to protoplanetary disks (PPDs) around young stellar objects (YSOs). Radiative transfer models of PPDs are able to successfully reproduce both the SED and infrared interferometric measurements on the few pAGB targets studied so far (Hillen et al 2014(Hillen et al , 2015Kluska et al 2018). As the PPDs are well studied both observationally and theoretically, the very close similarity with the disks around pAGB binaries points toward a potential universality of physical processes in dusty circumstellar disks occupying a different parameter space (i.e.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations